Ongoing transmission of Entamoeba histolytica among newly diagnosed people living with HIV in Taiwan, 2009-2018. - Sung-Hsi Huang; Mao-Song Tsai; Chun-Yuan Lee; Chin-Shiang Tsai; Chun-Eng Liu; Yuan-Ti Lee; Hong-An Chen; Ling-Ya Chen; Yu-Man Lu; Wan-Chen Tsai; Wei-Ting Hsu; Wang-Da Liu; et al. (Public Library of Science (PLoS), 2020)
Recent outbreaks of enterically transmitted infections, including acute hepatitis A and shigellosis, have raised the concerns of increasing Entamoeba histolytica infection (EHI) among people living with HIV (PLWH) in Taiwan. This study investigated the prevalence of EHI, its temporal trends, and associated factors among newly diagnosed PLWH in Taiwan. Medical records of newly diagnosed PLWH at six medical centers in Taiwan between 2009 and 2018 were reviewed. The annual prevalence of invasive amoebiasis and seroprevalence of E. histolytica were determined and examined by the Cochran-Armitage test. The clinical characteristics associated with invasive amoebiasis and seropositivity for E. histolytica were analyzed in multivariable regression models. Among 5362 patients seeking HIV care at six medical centers in Taiwan during the 10-year study period, 119 (2.2%) had invasive amoebiasis at the time or within six months of their HIV diagnosis. Among 3499 who had indirect hemagglutination antibody (IHA) determined, 284 (8.1%) had positive IHA (≥1:32) and 205 (5.9%) had high-titre IHA (≥1:128). The prevalence of invasive amoebiasis increased from 1.3% in 2012 to 3.3% in 2018 (p = 0.024). Invasive amoebiasis was independently associated with a greater age, men who have sex with men, rapid plasma reagin titre ≥1:4, and concurrent shigellosis and giardiasis. Increasing prevalence of invasive amoebiasis among newly diagnosed PLWH in Taiwan calls for strategies to prevent ongoing transmission in this population. Routine screening of EHI for early diagnosis and treatment is recommended, especially among men who have sex with men and those who present with other sexually or enterically transmitted infections.